2022
DOI: 10.1007/s00401-022-02452-1
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the neurovascular unit unveils detrimental effects of osteopontin on the blood–brain barrier in acute ischemic stroke

Abstract: Blood–brain barrier (BBB) dysfunction, characterized by degradation of BBB junctional proteins and increased permeability, is a crucial pathophysiological feature of acute ischemic stroke. Dysregulation of multiple neurovascular unit (NVU) cell types is involved in BBB breakdown in ischemic stroke that may be further aggravated by reperfusion therapy. Therefore, therapeutic co-targeting of dysregulated NVU cell types in acute ischemic stroke constitutes a promising strategy to preserve BBB function and improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 134 publications
3
46
0
Order By: Relevance
“…We showed previously that osteopontin is highly expressed in the extracellular space and in the major NVU cells (endothelial cells, pericytes, astrocytes and microglia) both in acute human and murine ischemic stroke lesions. We also showed that osteopontin unfolds deleterious effects on BBB function in a mouse model of acute ischemic stroke, further supporting brain edema formation and increasing the risk for hemorrhagic transformation 12 . CD44, a receptor for osteopontin 16 , which is a crucial osteopontin signaling pathway member, was also significantly upregulated in all major NVU cell types in acute murine ischemic stroke based on our recently published transcriptomic dataset 12 .…”
Section: Resultssupporting
confidence: 53%
See 4 more Smart Citations
“…We showed previously that osteopontin is highly expressed in the extracellular space and in the major NVU cells (endothelial cells, pericytes, astrocytes and microglia) both in acute human and murine ischemic stroke lesions. We also showed that osteopontin unfolds deleterious effects on BBB function in a mouse model of acute ischemic stroke, further supporting brain edema formation and increasing the risk for hemorrhagic transformation 12 . CD44, a receptor for osteopontin 16 , which is a crucial osteopontin signaling pathway member, was also significantly upregulated in all major NVU cell types in acute murine ischemic stroke based on our recently published transcriptomic dataset 12 .…”
Section: Resultssupporting
confidence: 53%
“…We also showed that osteopontin unfolds deleterious effects on BBB function in a mouse model of acute ischemic stroke, further supporting brain edema formation and increasing the risk for hemorrhagic transformation 12 . CD44, a receptor for osteopontin 16 , which is a crucial osteopontin signaling pathway member, was also significantly upregulated in all major NVU cell types in acute murine ischemic stroke based on our recently published transcriptomic dataset 12 . Interestingly, CD44 has been reported to promote detrimental effects in cerebral ischemia 15 and impairment of BBB integrity in vitro 17 , 18 .…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations